Antibacterial invitroand antidiarrhea invivoeffects of the infusion of sago roots (Metroxylon sagu) - Mohammad Bakhriansyah; Aswin Febria; Defiyanti Rahmah (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Fresh root of sago (Metroxylon sagu) traditionally has been used as an antidiarrhea in South Kalimantan community. However, there is no scientific data yet to support it. The aims of this study were to investigate the antibacterial effect of the infusion of sago root on Salmonella typhi(S. typhi) as one of bacteria causing diarrhea in vitro and to find out its effects as anti diarrhea in male mice induced by castor oil in vivo. This experimental study measured the inhibitory zone in S. typhiculture and to count the frequency and duration of diarrhea. It used 3 concentrations, i.e 10%; 20% and 40% of the infusion of sago root. Chloramphenicol and aquadest were used as positive and negative control groups respectively in in vitro study, whereas in in vivo one loperamide was positive control group. Chloramphenicol was used since it is an antibiotic standard for eradicating S. thypi, whereas Loperamide is anti peristaltic agent from declining the frequency and duration of diarrhea. The infusion inhibited radical zone of S. typhi culture by 7.8; 9.8 and 10 mm, decreased the frequency of diarrhea 24.23%; 40.54% and 16.22% and decreased the duration of diarrhea 26.69%; 52.92% and 10.27% at concentration 10%, 20% and 40%, respectively. As conclusion the infusion of sago root has the potency as anti bacteria and decrease the frequency and duration of diarrhea. The best concentration of the infusion of sago root is 20%.Key words: Metroxylon sagu, Mice, Anti diarrhea, Anti bacteria